Energy Efficiency Optimization Design of a Forward-Swept Axial Flow Fan for Heat Pump - Yang, Ke; Zhou, Shuiqing; Hu, Yinjie; Zhou, Huaxin; Jin, Weiya (Frontiers in Energy Research, 2021)
As one of the key components of the heat pump system, compared to that of a conventional axial fan, the blade tip area of a forward-swept axial fan is much larger than its blade root, which is the main noise source of the fan and also has an important influence on the fan efficiency. Enhancement of the aerodynamic performance and efficiency of a forward-swept axial fan was addressed by utilizing the Bezier function to parameterize the forward-swept curve on blade tops. In order to quickly select an agent model suitable for the project, an ES model was established by integration of the RBF model and the Kriging model. While the NSGA-II algorithm was combined and multi-objective optimization was carried out with the flow rate and total pressure efficiency as optimization goals. Analysis of optimization results revealed that the optimized axial flow fan’s flow rate and total pressure efficiency were improved to some degree. At the design working point, the fan’s flow rate increased by 1.78 m³/min, while the total pressure efficiency increased by 3.0%. These results lay solid foundation for energy saving of heat pump system.